Cidade universitária da UFMG: um território urbano num campus? - Eduardo Fajardo Soares (2016)
This dissertation aims to study the birth of Universidade Federal de Minas Gerais` University City, its consolidation in Campus Pampulha, its development, history, memory, conflicts, and rationality. The main research instruments were primary and secondary sources, interviews, surveys and images. The core of this research is to seek if there is a conflict between Campus Pampulha reallly becoming an University City, with urban insertions and characteristics, or a virtual bubble of knowledge, with particular performances pointing to contradictory and tight scientific and cultural productions, isolated from urban context.